Effectiveness of the Multi-Representation Discourse Learning Model on Mathematical Problem-Solving Ability and Self-Confidence - Safitri, Nurlia; Raupu, Sumardin; Arifanti, Dwi Risky; Megasari, Megasari; Thalhah, Sitti Zuhaerah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study investigated the effectiveness of the Multi-Representation Discourse (DMR) learning model in improving students’ mathematical problem-solving skills and self-confidence. A quasi-experimental pretest–posttest control group design was applied to 55 students selected through cluster random sampling from a population of 194. Data were collected using observation sheets, problem-solving tests, and self-confidence questionnaires, and analyzed with descriptive and inferential statistics. The results revealed that the DMR model was effectively implemented and significantly enhanced both mathematical problem-solving abilities and self-confidence compared to conventional instruction. Beyond its practical effectiveness, this study contributes to the theoretical discourse by demonstrating the value of multi-representation integration in mathematics learning, and provides empirical evidence that discourse-oriented strategies can strengthen both cognitive and affective outcomes. These findings underscore the potential of the DMR model as a pedagogical innovation for advancing mathematics education.